Hill recreational and services valuation : a case study of Taman Melawati Hill - Pek, Chuen Khee; Tee, Chee Hoong; Ng, Phuay Ying (Sunway University College, 2010)
This study estimates the economic values of household preference for preservation and conservation of hill recreational and services values in Malaysia. The Contingent Valuation technique is employed on 100 randomly selected households in the vicinities of Taman Melawati Hill. The study finds that hill preservation is important and the public is willing to pay for initiatives to mitigate further degradation to this ecosystem. More specifically, the study ascertains that households on average are willing to donate MYR92.40 per annum to the trust fund for hill mitigation management initiatives. This value conveys a total economic value of MYR51.6 million per annum, based on the Selangor state population who are willing to pay for the mitigation cause. This substantial value can help policy makers to identify any mismatch between what the public actually demands and are willing to pay for and the degradation to the supply due to modern developments.